Characterization of biomimetic calcium phosphate labeled with fluorescent dextran for quantification of osteoclastic activity. (1st July 2015) - Maria, Salwa M.; Prukner, Christiane; Sheikh, Zeeshan; Müller, Frank A.; Komarova, Svetlana V.; Barralet, Jake E.
Graphical abstract: Abstract: Bone resorbing osteoclasts represent an important therapeutic target for diseases associated with bone and joint destruction, such as rheumatoid arthritis, periodontitis, and osteoporosis. The quantification of osteoclast resorptive activity in vitro is widely used for screening new anti-resorptive medications. The aim of this paper was to develop a simplified semi-automated method for the quantification of osteoclastic resorption using fluorescently labeled biomimetic mineral layers which can replace time intensive, often subjective and clearly non-sustainable use of translucent slices of tusks from vulnerable or endangered species such as the elephant. Osteoclasts were formed from RAW 264.7 mouse monocyte cell line using the pro-resorptive cytokine receptor activator of nuclear factor kappa-B ligand (RANKL). We confirmed that fluorescent labeling did not interfere with the biomimetic features of hydroxyapatite, and developed an automated method for quantifying osteoclastic resorption. Correlation between our assay and traditional manual measurement techniques was found to be very strong ( R 2 = 0.99). In addition, we modified the technique to provide depth and volume data of the resorption pits by confocal imaging at defined depths. Thus, our method allows automatic quantification of total osteoclastic resorption as well as additional data not obtainable by the current tusk slice technique offering a better alternative for high throughput screening of potential antiresorptives.